Optimized Extraction and Characterization of Folates From Date Palm Fruits and Their Tracking During Fruits Wine Fermentation - Meng, Ziyi; Yi, Ling; Hu, Qingxin; Lin, Zhiyi; Ramaswamy, Hosahalli S.; Wang, Chao (Frontiers in Nutrition, 2021)
Folates belong to the essential B vitamins group and participate in one-carbon metabolism. Date palm fruits (Phoenix dactilyfera L. family Arecaceae) are consumed by millions of people and are good sources of folates. To date, no detailed study has been carried out on suitable methods for folate extraction from date palm fruits. In the present study, an experimental design using response surface methodology (RSM) was used to maximize the extraction yield of folates from date palm fruits by including enzymatic depectinization. By applying this new strategy and a UHPLC-MS/MS technique for analysis, total folate and different folate vitamers of three cultivars of date palm fruits (Muzafti, Zahdi and Rubai), brewer's yeast and fermented date wine were analyzed. The optimized extraction conditions of folates from date palm fruits were found to be a pectinase activity of 47.7 U, an incubation temperature of 40 °C and an incubation time of 38 min, which yielded a total folate content of 191-301 µg/100g. In brewer's yeast, the extracted total folate content was very high (4870 g/100g), and in the resulting date wine, it reached a maximum of 700 g/L on the fifth day. The predominant folate vitamers in date fruit and fruit wine were 5-formyltetrahydrofolate (5-CHO-THF) and 5-methyltetrahydrofolate (5-CH3-THF). During date palm fruit fermentation for up to 8 days, the 5-CHO-THF content gradually decreased by 20%, while 5-CH3-THF increased linearly from day 1 to day 5 (y=0.058x+0.0284, R2=0.9614). This study shows that date palm fruit and fruit wine are excellent sources of folate, and further study can be focused on different methods to improve folate stability during wine storage.